PENGELOLAAN WARISAN BUDAYA BERWAWASAN LINGKUNGAN: STUDI KASUS PENGELOLAAN LIVING MONUMENT DI BALI - I Nyoman Wardi (Bumi Lestari Journal of Environment, 2008)
The living monument in Bali (candi, pura/temple, hermitage cave, etc) has various functions. Since it was built, its function was dominated for religious purpose, especially to pay homage for god/goddess, ancestors, and other holy spirits. The praying purposed to ask for safety and peace, fertility, prosperity, welfare of the followers and the villagers. Besides that function, monument and its environment also utilized to enhance the historical and socio-cultural awareness and science development, and it is also useful for social integration, economic and ecological function. Recently those functions are still maintained and developed on line with socio-cultural and environmental changes. Related to socio-religious function with all of its rituals, later on cultural heritage become a prominent of tourism interest ( destination) in Bali. Besides that, the sacred value of the monument indirectly brings impact to environmental conservation. The conservation of natural environment then contributes to fulfill the monument needs for ritual and building construction. But recently, there is a new trend arising to communities related to cultural values which is showed by behavioral change on heritages conservation. The carelessness of environmental control and conservation, has caused degradation on quality of heritage and its environment. The degradation of ecological and magic-religious values, indirectly will affect the degradation of peace, prosperity and welfare of local communities , and then they are followed by lack of awareness and concern on cultural and natural heritages conservation. In order to cope with the problem, an holistic-integrated approach needs to be applied to manage living monument and its environment in Bali by appreciation on stability and proportional functions of socio-cultural, economic, and ecological aspect in frame of sustainable development.